Subcutaneous fat necrosis associated with hypercalcemia in neonates with neonatal encephalopathy treated with therapeutic hypothermia. Issue 4 (August 2021) - Rodd, Celia; Schwieger-Briel, Agnes; Hagmann, Cornelia
Abstract: Subcutaneous fat necrosis of the newborn (SFNN) is a rare, self-resolving panniculitis. The onset of skins lesions occurs within the first week of life, with a median age of onset around day 6 of life (range 1–70). About 50% of neonates with SFNN will develop hypercalcemia in the first month though some present later. Typically, SFNN develops prior to hypercalcemia. Only half of the neonates have classic symptoms of hypercalcemia; routine screening for hypercalcemia is recommended for neonates with SFNN or at-risk. The mechanism for hypercalcemia is usually aberrant 1, 25-dihydroxyvitamin D synthesis in the necrotic tissue increasing intestinal absorption of calcium. Prompt recognition and treatment is required, often in hospital. Treatment options are low calcium-vitamin D formula or sometimes intravenous bisphosphonates. Regular monitoring post-intervention is required when normalizing the diet. Outcomes are good with routine surveillance and interventions. A multidisciplinary team approach (neonatologists, pediatric endocrinologists and nephrologists, dieticians) is optimal.